“I’m pulling through because of you”: injured workers’ perspective of workplace factors supporting return to work under the Saskatchewan Workers’ Compensation Board scheme - Lewis, Ian; Houdmont, Jonathan (Frontiers in Rehabilitation Sciences, 2024)
Research demonstrates sustained return to work (RTW) for workers individuals on medical leave is the product ofinfluenced by personal and job resources and job demands. Relatively few studies have been conducted in the workers' compensation context that is known to have longer absence durations for RTW.This study sought to illuminate workers' experience as they returned to work following a serious work injury that was either psychological in nature or involved more than 50 days of disability, with a focus on the co-worker, supervisor, and employer actions that supported their return.Workers in Saskatchewan, Canada, with a work-related psychological or musculoskeletal injury, subsequent disability, and returned to work in the last three years, were invited to complete an online survey comprising free-text questions. Thematic analysis was used to explore participants' experience.Responses from 93 individuals were analyzed. These revealed that persistent pain, emotional distress, and loss of normal abilities were present during and beyond returning to work. Almost two-thirds indicated that supervisor and co-worker support was critical to a sustained return to work: their needs were recognized and they received autonomy and support to manage work demands. In contrast, one third indicated that support they expected and needed from supervisors and employers was lacking. Employers were viewed as unimportant to return to work success.